Twist Drill Aspiration of Pyogenic Brain Abscesses: Our Experience in 103 Cases - Singh, Ishwar; Rohilla, Seema; Kumawat, Manjulata (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background Intracranial abscesses remain a significant health care problem in developing countries. Though potentially curable, brain abscess remains a diagnostic and therapeutic challenge. The effective treatment of intracranial abscess remains controversial. Various surgical procedures like drainage, aspiration, and excision have been advocated for the management of brain abscess with variable results. Aspiration is a rapid and safe procedure, especially with use of stereotactic techniques, intraoperative ultrasound, or computed tomography (CT) scan guidance. However, these are not readily available everywhere.Objective To assess the outcome in pyogenic brain abscesses treated by twist drill aspiration (a bedside procedure) in which point of aspiration is marked with the help of three-dimensional (3D) reconstructed CT images.Methods From September 2007 to September 2011, a total of 103 cases of brain abscesses over 2.5 cm in size were treated by twist drill aspiration. The point of aspiration was marked with the help of 3D reconstructed CT images using fixed bony landmarks as reference, and exact measurement were taken with the help of biopsy software.Results In the present study, 103 cases of superficial brain abscesses were treated via twist drill aspiration. Out of these, 98 patients had a single abscess and five had multiple abscesses. Out of the 103 patients, 86 (83.4%) showed good recovery, 9 (8.7%) had moderate disability, 3 (2.9%) had severe disability, and 5 (4.8%) expired.Conclusion Twist drill aspiration is a rapid, safe, and very effective lifesaving procedure in the underdeveloped world where stereotaxy is not readily available.
Keywords: brain abscess; twist drill aspiration; minimally invasive technique